Percepções dos agentes comunitários de saúde sobre a segurança do paciente - Musmanno, Luiz Henrique Fernandes (2015)
This study aimed to analyze the perception of community health agents of the Northwest Sanitary District in the city of Goiania on patient safety. This is a descriptive, exploratory, qualitative quantitative nature developed with 169 community workers Health Centers of Health of the Family of Northwest region of the city of Goiânia, Goiás. Data collection was preceded by educational workshops on security patient, directed to professionals who made up the sample universe for which we used a self-administered instrument to evaluate the perception of patient safety. The data were systematized through descriptive and thematic. Of the participants, 93.5% were female; aged between 19-63 years; 63.3% had completed high school. Operating time as community health worker varied from one month to 16 years; 73% had heard about patient safety and 96% felt safe with the quality of information provided to users. Regarding knowledge of incidents occurring in healthcare facilities, only 37% identified their occurrence. The main cause of incidents, the perception of this sample refers to the lack of communication; medication errors and fall of the patient. The profile of users who request more information were, respectively, the elderly, hypertensive, diabetic and pregnant women. It was observed that the theme patient safety a novelty in the family health strategy, especially with community health workers. The study points to the need for socialization of this approach with professionals from other health teams, in order to expand its training and transfer of knowledge in service to the population, which has the ability to collaborate with the prevention of incidents. There is need to expand educational strategies as a way to reach the health care, skilled and safe, as recommended by the Brazilian health system.